2001
DOI: 10.1111/j.1651-2227.2001.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination rate and age of premature infants weighing <1500 g: a pilot study in north‐western Switzerland

Abstract: In Switzerland, there are no special vaccination recommendations for premature and low‐birthweight infants with respect to a particular target vaccination age. Incomplete and delayed vaccination bears the inherent risk of preventable infections. Therefore, the vaccination rate and age of 60 premature infants in north‐western Switzerland born in 1994/95 were investigated in a retrospective case‐control study. For this group of patients these are the first data ever available for this region. At the age of 4–5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
0
18
1
5
Order By: Relevance
“…This shows a clear learning effect on physicians that treat these infants. Tillmann et al 7 reported in a group of premature babies in north-western Switzerland a significant delay when compared with full-term controls. This delay was mostly caused by insufficient information to parents about the importance of adequate timing of the vaccination, and the authors speculate that practitioners still believed that pre-term babies should be vaccinated according to their corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…This shows a clear learning effect on physicians that treat these infants. Tillmann et al 7 reported in a group of premature babies in north-western Switzerland a significant delay when compared with full-term controls. This delay was mostly caused by insufficient information to parents about the importance of adequate timing of the vaccination, and the authors speculate that practitioners still believed that pre-term babies should be vaccinated according to their corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…Deshalb empfehlen Expertengremien wie die STIKO am Robert-Koch-Institut in Berlin, aber auch amerikanische und britische Impfkommissionen, Fr ü hgeborene nach dem chronologischen Alter zu impfen. Erhebungen au ß erhalb Deutschlands konnten bisher zeigen, dass Impfungen bei Fr ü hgeborenen oftmals versp ä tet und mit gro ß en Bedenken durchgef ü hrt werden [5,13,24] . Diese Bedenken zeigten auch die Reaktionen in verschiedenen Internetportalen nach einem Aufruf der Deutschen Gesellschaft f ü r Sozialp ä diatrie und Jugendmedizin (DGSPJ) ab Mai 2009, Fr ü hgeborene zeitgerecht zu impfen.…”
Section: Diskussion ▼unclassified
“…Es wurde jedoch darauf hingewiesen, dass Eltern leichte Impfnebenwirkungen eventuell nicht erkannt oder nicht angegeben haben und sich dadurch niedrigere Raten an Nebenwirkungen ergeben k ö nnen als tats ä chlich aufgetreten seien. Ä hnlich verh ä lt es sich in unserer Darstellung von aufgetretenen Nebenwirkungen, da sie sich auf die Aussagen der Eltern st ü tzt und somit keine objektivierte Erfassung ist [24] . Vergleichbare Erkenntnisse bez ü glich der versp ä teten Durchf ü hrung der Impfungen ergab eine Studie aus den USA, die gleichfalls eine sig nifi kante Verz ö gerung der Impfungen bei sehr und extrem Fr ü hgeborenen nachweisen konnten [13] .…”
Section: Diskussion ▼unclassified
“…Missed preventive visits, and difficulties in tracking undervaccinated patients play a major role in lacking compliance with recommendations [21]. In addition, children with preexisting medical conditions such as premature birth are vaccinated more reluctantly than full-term born children [22].…”
Section: Introductionmentioning
confidence: 99%